Enhancing maternity healthcare workers’ wellbeing using insider participatory action research - Claire M. Wood; Mary Chambers; Jayne E. Marshall (BMC Health Services Research)
Abstract Background Good healthcare worker (HCW) wellbeing positively impacts service user outcomes, yet the United Kingdom (UK) National Health Service (NHS) is suffering workforce burnout and retention issues. While urgently needing evidence-based wellbeing strategies, participatory interventions using positive psychology have been under-investigated. We aimed to develop a caring, collegial NHS labour ward environment wherein HCWs created paths to enhancing individual and collective workplace wellbeing. Methods Insider Participatory Action Research (IPAR) used positive psychology within a social constructionist, pragmatic approach. All clinical and non-clinical HCWs on a consultant-led labour ward in the East Midlands, England, UK were invited to identify current sources of workplace wellbeing on which to collectively construct future ways of working. Qualitative data from several methods (below) were inductively thematically analysed. Results Between October 2018 and July 2020, data were generated from 83 paper and 13 online questionnaires; 59 interviews; three action groups; six peer participant reviewers; 16 comments on data displays; and three emails. Three themes represented sources of workplace wellbeing: emotional, professional, and physical nourishment. Culture shifted to be more compassionate and inclusive, and morale, positivity, and atmosphere improved. Ways of working changed. Colleagues more proactively cared for each other, worked well together in teams, expressed thanks and feedback, and instigated interventions for colleagues’ and women’s welfare. Participants proposed that IPAR activities prompted change including: the researcher being considered an accessible colleague wellbeing resource; raised awareness of the importance of HCW wellbeing; and strengthened HCW relationships. The HEARS wellbeing intervention model (HCW driven, Everyone involved, Ask what makes a person feel good at work, Responses displayed, Steps taken) was developed to frame processes by which HCW participation catalysed impact towards workplace wellbeing. Conclusions To our knowledge, this is the first English language study using IPAR to enhance HCW wellbeing. Colleagues from diverse occupational groups improved individual and collective wellbeing through self-determined action. Using participatory methodology and positive psychology encouraged a more compassionate and inclusive culture. Subject to implementation research evaluating these strategies’ impact in different settings, we propose the HEARS wellbeing intervention model and workplace-based Colleague Support Volunteers as actions towards wellbeing and retention in healthcare organisations.